Exploring the potential of wild food resources in the Mediterranean region: natural yield and gathering pressure of the wild asparagus (Asparagus acutifolius L.) - Molina, M.; Pardo-de-Santayana, M.; García, E.; Aceituno-Mata, L.; Morales, R.; Tardío, J. (Spanish Journal of Agricultural Research, 2012)
In the Mediterranean region, some wild edible species such as Asparagus acutifolius L. are still harvested and even marketed. Considering the great interest of this species, including its recreational, commercial and agronomic uses, we aimed to study its natural supply and its current scale of harvesting. Nearly 50 plants were monitored in two sites of Central Spain. An experimental harvest of 100% of spears was conducted during spring 2008-2009 to estimate spear production per plant and per hectare. Plants were also monitored but not harvested in 2010-2011 at Site 1 to document real gathering practices and its influence on yield. Spear production ranged from 5.0 to 12.8 g per plant and from 4.0 to 8.9 kg ha-1, reaching the top-ranked values in May (30-60% of total yield). Between-site variations on yield were mainly related to spear number rather than to spear weight, whereas weather conditions influenced annual yields. The percentage of plants harvested by local foragers varied from 26 to 47%. A slight but not significant trend for collecting the largest spears was recorded. According to spear number in harvested (1.8-2.5 spears) and non-harvested plants (1.3-1.5 spears), gathering seemed to promote the growth of new spears, although further research is needed to assess its influence in the long term. Results suggest that foraging is a time-consuming practice, thus social and cultural factors may explain its high appreciation in present times.